Acta Universitatis Danubius. Œconomica, Vol. 15, No. 1 - 1: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
This paper provides a review of the firm-NPO- recipient model that helps develop the economy of South Africa highlighting the regulatory environment of South Africa which encourages many firms to use their corporate social responsibility (CSR) efforts to develop national skills and infrastructure. In South Africa, an often chosen vehicle for delivery of CSR, is a nonprofit intermediary organisation (an NPO). NPOs play an important transitional management role in mutual value creation linking firms to CSR recipient communities. NPOs are each a specialist in a specific skill or community infrastructure delivery requirement, additionally acting to highlight community needs for a CSR intervention, to firms. Notwithstanding the contribution of NPOs to many developing African countries economies, studies as to what criteria in their working environment facilitate the NPOs to do their work as intermediaries, is limited especially for South Africa. This paper reviews the legislative contextual environment of NPOs in relationships for CSR delivery with business firms in South Africa highlighting how this enables both the nonprofit NPO and profit driven firm, to participate in the economic development of South Africa.